Autocatalysis in Eschenmoser Coupling Reactions - Duez, Quentin; Marek, Lukáš; Váňa, Jiří; Hanusek, Jiří; Roithová, Jana (Chemistry (Weinheim an der Bergstrasse, Germany), 2024)
The Eschenmoser coupling reaction (ECR) of thioamides with electrophiles is believed to proceed via thiirane intermediates. However, little is known about converting the intermediates into ECR products. Previous mechanistic studies involved external thiophiles to remove the sulfur atom from the intermediates. In this work, an ECR proceeding without any thiophilic agent or base is studied by electrospray ionization-mass spectrometry. ESI-MS enables the detection of the so-far elusive polysulfide species Sn , with n ranging from 2 to 16 sulfur atoms, proposed to be the key species leading to product formation. Integrating observations from ion mobility spectrometry, ion spectroscopy, and reaction monitoring via flow chemistry coupled with mass spectrometry provides a comprehensive understanding of the reaction mechanism and uncovers the autocatalytic nature of the ECR reaction.
Keywords: Reaction mechanisms; Density functional theory calculations; Vibrational spectroscopy; Ion mobility; Mass spectrometry; Autocatalysis; Flow chemistry